Measurements of the top-quark mass using charged particle tracking - Aaltonen, T; Adelman, J; Akimoto, T; Alvarez Gonzalez, B; Amerio, S; Amidei, D; Anastassov, A; Annovi, A; Antos, J; Apollinari, G; Apresyan, A; Arisawa, T; et al. (2010)
We present three measurements of the top-quark mass in the lepton plus jets channel with approximately 1.9fb-1 of integrated luminosity collected with the CDF II detector using quantities with minimal dependence on the jet energy scale. One measurement exploits the transverse decay length of b-tagged jets to determine a top-quark mass of 166.9-8.5+9.5(stat)±2. 9(syst)GeV/c2, and another the transverse momentum of electrons and muons from W-boson decays to determine a top-quark mass of 173.5-8.9+8.8(stat)±3. 8(syst)GeV/c2. These quantities are combined in a third, simultaneous mass measurement to determine a top-quark mass of 170.7±6.3(stat)±2. 6(syst)GeV/c2. © 2010 The American Physical Society.